Inclusive and Participatory Policymaking at the Local Level: Problems and Possibilities - Levac, Leah; Gillis, Jacqueline (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2025)
Municipalities are being called on to become more participatory in their approach to policy making and governing. Concurrently, they are working toward making their policies, programs, and staff complements more inclusive and equitable, and more responsive to the ongoing consequences of colonialism and other forms of systemic discrimination. These developments share common normative and theoretical foundations, but municipalities are not necessarily actively working on these changes in tandem. In response, we ask, “What are the problems and possibilities that emerge in efforts to centre Indigenous Knowledges and intersectional commitments in participatory policymaking processes at the local level?” We highlight two barriers that arise persistently in these efforts and suggest modest ways forward that will be useful for municipal public servants working on community engagement; diversity, equity, inclusion efforts; and building relationships with Indigenous residents.